Effect Of Pod Storage And Fermentation Durations Using Shallow Box On The Quality Of Cocoa (Theobroma Cacao L.) Beans - Sulaiman, Khairul Bariah (2018)
Fermentation is important for the formation of flavour and colour precursor in the cocoa beans which are influenced by various factors including post-harvest practices. Therefore, the effect of pod storage and fermentation duration using a shallow box on the Malaysian cocoa beans was investigated. Physicochemical changes in wet cocoa beans and quality of the resulting dried cocoa beans were evaluated using a 4 x 6 complete randomized design with pod storage (0, 2, 4 and 6 days) and fermentation duration (0, 24, 48, 72, 96 and 120 hours) as the principal factors. The resulting dried cocoa beans were further characterized for profiles of colour and volatile compounds using the spectrophotometer, high-performance liquid chromatography-variable wavelength detector and solid-phase microextraction-gas chromatography-mass spectrometry. The results showed that the pod storage for four and six days were significantly (p < 0.05) influenced most of the physicochemical changes especially the mass temperature which had increased exceeding 42 °C within 24 hours of fermentation compared to without storage or pod storage for two days. The quality of dried cocoa beans produced significantly improved with the beans from the pod storage for four and six days had achieved respective scores of equivalent percent of fully brown 76.2% and 68.9% which indicated a well degree of fermentation as early as 24 hours compared to 48 hours from the pods without storage (65.5%) and storage for two (78.6%) days.